Theoretical substantiation of human resource management from the perspective of work and organisational psychology - Niclas Schaper (Management Revue, 2004)
In the article it is tried to substantiate further developments in human resource management with reference to the competency approach in work and organisational psychology. First the objectives of scientific and applied research in work and organisational psychology are lined out. Then the competency approach is discussed as a helpful concept to different challenges of human resource management. With reference to this assumption three different theoretical and methodological perspectives are introduced which focus on different aspects of understanding, analysing, diagnosing and developing competencies. These include the action and self-organisation theory perspectives of competencies and the competency modelling perspective.
Keywords: 650; work and organisational psychology; action theory; self-organisation theory; competency modelling approach; competency based human resource management; Personalmanagement; Arbeitspsychologie